Dieta habitual e fatores de risco para doenças cardiovasculares - Cervato, Ana Maria (1997)
INTRODUCTION: A survey by sampling in a county of the State of S. Paulo in 1990 sought, by means of home interviews, to analyse the habitual diet and risk factors for cardiovascular disease of people over 20 years of age. METHODOLOGY: Of the sub-specimen of a comprehensive study population, 557 individuals, aged between 20 and 88, were interviewed. The habitual diet, characterized by the dietary history, was compared with the recommendations on energy and nutrients of the WHO and the risk factors (obesity, lipemic disorders and diabetes mellitus) diagnosed by the Body Mass Index and biochemical measurements. RESULTS AND CONCLUSION: It was observed that 60% of the population consume a diet with total energy below the estimated need and that the caloric contribution of carbohydrates was of 56%, of the lipids 29% and of the proteins 15%. However, by percentil analysis, the caloric contribuition of lipids and of proteins was far above the recommended levels to the detriment of the carbohydrates. Energy, caloric distribution and quantity of cholesterol were satisfactory in only 5% of diets. Among the risk factors for the cardiovascular disease studied, obesity was found to be present in 38% of individuals, lipemic disorders in 26% and diabetes mellitus in 5%. Preponderantly light physical activity together with unsatisfactory diet, both in qualitative as in quantitative terms, aggravated this scenario still further.